Effect of inoculum source (sheep or goat rumen fluid) on in vitro digestibility and gas production kinetics of the foliage of some Spanish browse plants - Ammar H.; Ranilla M.J.; Tejido M.L.; Ovejero F.J.; González J.S.; López S. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
In vitro dry matter digestibility (IVD) and gas production kinetics in sheep and goat rumen fluid were determined for foliage of Erica australis, Cistus laurifolius, Quercus pyrenaica and Rosa canina. IVD was measured by first incubation in buffered rumen fluid and extraction with neutral detergent solution. Samples were also incubated in bottles, measuring gas volumes. IVD was not different between sheep and goats. Gas production was higher in sheep for E. australis and C. laurifolius, and in goats for Q. pyrenaica. Gas production was faster in goats for Q. pyrenaica and R. canina, and in sheep for the other species. The extent of degradation of R. canina and Q. pyrenaica was higher in goats, with no differences between ruminants for the other species. These suggest interspecies differences in the in vitro ruminal fermentative activity between sheep and goats that could determine their ability to digest the foliage of shrubs.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)